Co-Culture Communication of Disabled Characters in the Movie Dancing in the Rain - Dwi Latifatul Fajri; Prahastiwi Utari; Pawito (Formosa Journal of Social Sciences (FJSS), 2024)
The film Dancing in the Rain tells the story of Banyu, a mentally retarded person who experiences discrimination and bullying. As a mentally retarded person, Banyu has limitations in interaction and communication. Even though he often gets bullied, Banyu has two friends who always support him, namely Radin and Kirana. This research aims to determine the communication strategies of disabled groups in the film Dancing in the Rain. The film shows several scenes of interaction and communication between disabled characters in society. The theory used in the research is Mark Orbe's Co-Culture to analyze communication strategies. This research uses qualitative methods for data collection. The analysis uses the descriptive method of the Charles Sanders Pierce Semiotics model. This semiotic model consists of three, namely representamen (sign), object, and interpretant. Researchers used 18 scenes in the film that show Banyu's interactions with friends and the community. The results of this research show that people with disabilities use non-assertive separation and non-assertive accommodation strategies. Apart from that, there was a change in communication, namely assertive accommodation. As a disabled person, Banyu is more sincere and open to his two friends Radin and Kirana